Oil prices and Malaysian economy - Abd Jalil, Norasibah; Mat Ghani, Gairuzazmi; Duasa, Jarita (World Business Institute, 2009)
This paper studies the impact of oil prices on GDP in Malaysia. In particular, three types of oil prices; world oil price (PW), world oil price in domestic currency (PWD), and domestic oil price (PD) are tested against the GDP within VAR framework. Based on the findings, change in PD oil price appears to have the most pronounced effect to the GDP. It is because, significant results of PD analysis are documented both in short-run and long-run tests. In the asymmetric test, significant result is documented in PD analysis only. The finding signifies the presence of asymmetric relationship between oil price changes and the economy. With these evidences we conclude that, policymakers may consider using PD oil price as a policy tool in the case oil price increase strikes again in the future. In the event policymakers are faced with policy options of either to increase or decrease the oil price, they should be aware that oil price decrease gives significant effect to the economy than oil price increase.